The Design of Modest Water Plan Building to Improve Scientific Process Skill - Syaifuddin Syaifuddin; Putut Marwoto; Sigit Priatmoko; Sarwi Sarwi (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2022)
This research aims to: (1) create a design of a modest water plan for mathematics lessons with the material of fluid, (2) describe the improved psychomotor skills of the learners from the learning process with the created design, the modest water plan, for mathematics lesson with the material of fluid, and (3) describe the learners' responses toward the design of the water pump with the lesson of fluid mechanics. This Research & Development applied the ADDIE model with five stages. The first stage was analysis. The researchers reviewed the physics learning problems for Senior High School learner levels, specifically in the chapter on fluid mechanics. The second stage was the designing stage. The researchers designed the experiment tools. The third stage was the development stage. The researchers provided the materials to experiment. The fourth stage was the implementation stage. The researchers used the pre-created tool in a trial run test. Then, the fifth stage was the evaluation stage. This stage involved the reliability test based on the data validity of the experiment results. The results showed that: (1) the design of the modest water pump was applicable as the media of fluid mechanics learning, (2) the pretest-posttest results of the trial run test showed the improved aspect of the learners' scientific process skills; and (3) the learners' responses toward the design as the learning media for fluid mechanics was categorized "excellent."